BIPA Teachers’ Strategies in Teaching Indonesia Vocabulary Online for Students Other Languages - Yessi Travolta; Syafryadin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
The Indonesian language program known as Indonesian Language for Foreign Speakers (BIPA) is designed for foreigners. One of the most crucial elements in using a second language successfully is vocabulary. The aims of this study were to identify the strategies that BIPA teachers employed to teach Indonesian vocabulary online and the factors that influenced the utilization of these strategies with foreign students. The study used a qualitative descriptive research design. The sample of this study consisted of 12 BIPA teachers at the University of Bengkulu. The result of this study revealed that there were five strategies used by BIPA teachers in teaching Indonesian vocabulary, namely: 1) Drilling, 2) Code-Switching, 3) Translation, 4) Guessing the context, and 5) Making Task. Additionally, the second outcome examined the factors that influenced the BIPA teacher's use of the strategies for teaching vocabulary in Indonesia; student abilities, duration of time, and the level of material.